Phenotypic methods for detection of metallo-β-lactamase (MBL) production in multidrug resistant gram negative bacilli – comparative study - Umesh Santlal Hassani; Rashmi Mahalle (Creative Pharma Assent, 2023)
Introduction: One of the most common mechanism of resistance of bacterial pathogens to β-lactam antibiotics is production of β-lactamase, there are different types of Beta lactamases, which are expressed by drug resistant gram-negative bacteria. Carbapenemases (Metallo beta lactamases/MBL) are the β-lactamases with the widest spectrum of activity. Early detection of MBL-producing organisms is crucial to establish appropriate antimicrobial therapy and to prevent their interhospital and intrahospital dissemination. Several phenotypic methods are available for the detection of MBL producing bacteria. As there is no standardized method present study was done to screen MDR gram negative bacilli isolated from clinical samples for MBL-production by a low cost, convenient and sensitive procedure. Methods: All non-duplicate MDR gram negative isolates obtained from various clinical samples were screened for carbapenam resistance. All carbapenam resistant bacteria were screened for production of MBL by 3 phenotypic tests (Double disc synergy, combined disk test, Hodge test). The results were compared and analyzed on the basis of results obtained by E test. Results: During Study Period, 988 non duplicate gram negative bacilli were isolated, 70.64% (698) were multi drug resistant. Amongst Total number of MDR Isolates to carbapenam resistance was seen in 62(9.28%). These 62 isolates that were resistant to carbapenam were tested for MBL production. 54 (87%) of these 62 isolates showed MBL production by disc potentiation test whereas 41 isolates (66%) gave positive result by DDST. By Modified Hodge test, out of 62, 48 isolates (77.4%) were MBL positive. Compared to E- test, the Sensitivity Specificity and Accuracy for Disc potentiation test was 90%,100% and 90.32%, for Modified Hodge test was 80%,100% and 80.6% and for Double disc synergy test was 68.3%,100% and 69.3%. Conclusion: In our study, in comparison to MBL E test, disc potentiation test is more sensitive than double disc synergy test and Modified Hodge test for detection of MBL phenotypically